WOMAN IN MUSLIM SOCIETY Problems of transformation of social and legal status - Malika Shermatova (Лучшие интеллектуальные исследования, 2023)
Abstract. In the modern world, more than half a billion women comply with the requirements of traditional Islamic norms, as they live in societies in which religious canons operate. In many Muslim countries, the role of women in family and social life, as well as the state of women’s rights in general, is viewed through the mirror of religion. In other words, the context of women's rights is determined on the basis of Sharia, as interpreted by traditionalist Muslim theologians through government legislation. And we must admit that the influence of religious dogma often has serious negative consequences for the social and legal status of women in these countries.